TNFR1, o maestro do processo inflamatório na infeção por Leishmania amazonensis - Leonardo Gomes Vaz (2021)
TNF is pleiotropic cytokine involved in inflammation, host defense, tissue degeneration, tissue regeneration among other functions. TNF acts through two cognate receptors. TNFR1 seems to be more effective against intracellular parasites, including Leishmania. Studies about L. major elucidated the TH1/M1-TH2/M2 dichotomy. TH2 cells, through IL-4 and IL-13 secretion, active macrophages through the IL-4 receptor alpha chain leading to the metabolization of L-arginina by arginase I and production of polyamines, required to parasite replication. So, TH2/M2 is a classical model of susceptibility. On the other hand, TH1 cells activate macrophages through IFN-ɣ, which induces iNOS expression. iNOS, metabolizes L- arginine into citrulline and nitric oxide (NO). NO is a leishmanicidal gas. So, TH1/M1 polarization is the classical model of resistance to Leishmania. Absence of TNF impairs signaling through its receptor and M1 activation, essential to control the parasite. However, what is the impact of TNFR1 on the infection by L. amazonensis? Our data reveal the importance of TNFR1 in iNOS and NO production expression by mononuclear phagocytes that leads to lesion control. Although expression of TNFR1 by wild type mice is not enough to eliminate the parasite, this receptor mediates control of parasite replication. Indeed, in Leishmania models of infection, sterile cure is not achieved. Recently NO was implicated in rewiring cells of the immune system by diminishing pro-inflammatory cytokine production that leads to the resolution phase of the inflammatory process. We observed a large inflammatory infiltrate, especially a larger number of lymphocytes at the site of infection in the absence of TNFR1. Furthermore, the few lymphocytes at the site of infection of wild type were regulatory T cells mainly, correlating with high levels of IL-10 at the chronic phase of infection. At the later time points macrophages present M2 phenotype, controlling immunopathology. We conclude that for successful clearance and wound healing during leishmaniasis, different phenotypes of macrophages need to appear coordinately in the appropriate time. TNF, through TNFR1, seems to act as this conductor.